Supply chain excellence : a handbook for dramatic improvement using the SCOR model - Bolstorff, Peter; Rosenbaum, Robert (AMACOM/American Management Association, 2012)
The supply chain methodology that Industry Week calls ""genius.""
Keywords: Business logistics.; elektronické knihy; electronic books